2018
DOI: 10.1007/s11011-018-0293-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine attenuates brain hypoxic-ischemic injury from apoptosis and oxidative stress: role of p-Akt/GSK3β/HO-1/Nrf-2 signaling pathway

Abstract: To investigate the potential neuroprotection of oxymatrine in hypoxic-ischemic injury in rat's brain and the associated underlying mechanisms, modified neurological severity scores (mNSS) for neurological functional deficits, 2,3,5-triphenyl-tetrazolium chloride (TTC) staining for infarct volume, TUNEL assay and flow cytometry analysis for apoptosis were assessed. The expressions of Akt, glycogen synthase kinase 3 beta (GSK3β), phosphorylated Akt (p-Akt), phosphorylated GSK3β (p-GSK3β), nuclear factor erythroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Pathogeneses of HIE have been studied a lot, such as endoplasmic reticulum stress [42], inflammation among white matter [43], or neuron apoptosis [44]. In recent years, autophagy has become the new target in various systems.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogeneses of HIE have been studied a lot, such as endoplasmic reticulum stress [42], inflammation among white matter [43], or neuron apoptosis [44]. In recent years, autophagy has become the new target in various systems.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt/GSK3β and ERK1/2 signaling pathways are involved in regulating a variety of cellular processes, such as cell proliferation, apoptosis, and oxidative stress. GSK3β is a downstream signaling molecule of Akt [41], and activation of Akt/GSK3β signaling inhibited oxidative stress and apoptosis in rats with cerebral hypoxic-ischemic injury [42]. Inhibition of MAPK/ERK and PI3K/Akt signaling was previously suggested to suppress angiogenesis in endometrial carcinoma [43].…”
Section: Discussionmentioning
confidence: 97%
“…GSK3 activity could be modulated by the site-specific phosphory-lation of GSK3β, for example, ser9 of GSK3β inhibits its activity 42. GSK3 signaling is involved in a number of cellular pathological and physiological process, including glucose regulation, inflammation, oxidative stress, and apoptosis 43,44. A lot of evidence has shown that both GSK3 isoforms were abnormally activated in the brains of postmortem AD samples and AD animal model,45,46 resulting in excessive Aβ formation and aggregation 47.…”
Section: Discussionmentioning
confidence: 99%